Detection of behavioural patterns in Olympic male taekwondo athletes - Menescardi, C.; Estevan, I. (Journal of Human Sport & Exercise, 2017)
The relationship between athletes` behaviours is relevant for developing defensive and offensive strategies. Traditionally, sequential analysis has been conducted to assess relationships between two behaviours (one considered as focal and the other as conditioned). The aim of the study was to examine Olympic taekwondo athletes` behavioural patterns by conducting sequential analyses of tactical actions in bouts. Seventy-five male matches of the London Olympic Games in 2012 were studied to analyse tactical actions: attack (direct and indirect), counterattack (anticipatory, simultaneous and posterior), defensive (cuts, blocks and dodges), and opening actions. A sequential analysis of 2 lags (i.e., actions) in both prospective and retrospective perspectives were conducted by using five focal behaviours (i.e., those considered as tactical scoring actions: direct and indirect attack, anticipatory, simultaneous and posterior counterattacks). The results showed different tactical sequences according to the type of action considered as focal in the analysis. Specifically, direct attacks and simultaneous counterattacks were the most frequently action used in competition. Sequential analyses confirmed the interchangeable pattern of attacking and counterattacking actions. Those analyses can provide an insight for athletes` patterns and tactical strategy training in taekwondo based on empirical data.